2014
DOI: 10.1038/ncomms5680
|View full text |Cite
|
Sign up to set email alerts
|

Electrifying photonic metamaterials for tunable nonlinear optics

Abstract: Metamaterials have not only enabled unprecedented flexibility in producing unconventional optical properties that are not found in nature, they have also provided exciting potential to create customized nonlinear media with high-order properties correlated to linear behaviour. Two particularly compelling directions are active metamaterials, whose optical properties can be purposely tailored by external stimuli in a reversible manner, and nonlinear metamaterials, which enable intensity-dependent frequency conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
84
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 37 publications
0
84
0
1
Order By: Relevance
“…3a. Instead of the regular χ (2) response intrinsic to non-centrosymmetric crystals and interfaces, here the effective second-order nonlinear effect is produced by the interplay between the ubiquitous third-order nonlinear susceptibility χ (3) and the applied control field (χ (3) E C → χ (2) eff ; refs [36][37][38]. Moreover, the 30-nm-thick dielectric spacer is split into two halves, 15 nm each, made of Si 3 N 4 and HfO 2 (Fig.…”
mentioning
confidence: 99%
“…3a. Instead of the regular χ (2) response intrinsic to non-centrosymmetric crystals and interfaces, here the effective second-order nonlinear effect is produced by the interplay between the ubiquitous third-order nonlinear susceptibility χ (3) and the applied control field (χ (3) E C → χ (2) eff ; refs [36][37][38]. Moreover, the 30-nm-thick dielectric spacer is split into two halves, 15 nm each, made of Si 3 N 4 and HfO 2 (Fig.…”
mentioning
confidence: 99%
“…However, a close inspection of these studies reveals that the observed transition is extremely localized and hinges on electrical current filaments, suggesting that this direct electrically induced transition may not be sufficient to enable detectable modulations in metamaterials. Recently, nano-engineered metals have been comprehensively used in metamaterial and plasmonic systems, because in addition to facilitating optical resonances their electrical conductivities enable complex functionalities for achieving plasmonic-enhanced electro-optic effects in both the linear and nonlinear regimes414243. Metadevices with intrinsically embedded electrical and optical functions are correspondingly referred to as ‘self-sufficient' or ‘self-contained'.…”
mentioning
confidence: 99%
“…As an example, a metamaterial can be designed to have a negative refractive index in order to provide "perfect imaging" [3][4][5][6][7] and simultaneously the impedance equal to that of vacuum in order to minimize optical reflection from the material's surface. Other extraordinary applications include optical cloaking devices [8,9], elements enhancing optical density of states and energy transfer [10,11] as well as coherence [12][13][14], and a variety of optical elements composed of dispersive and nonlinear materials [15][16][17].…”
Section: Introductionmentioning
confidence: 99%